Intergenerational Assistance to Adult Children: Gender and Number of Sisters and Brothers. (June 2015) - Goodsell, Todd L.; James, Spencer L.; Yorgason, Jeremy B.; Call, Vaughn R. A.
This study considers how the number of sisters and brothers affects the flow of aid from older parents to adult children. Using data from the 2004 Middletown Kinship Survey ( N = 338), the authors find that the aid adults receive from their parents varies by the gender composition of the sibship. Adults with more sisters tend to receive less assistance from their older parents. This holds true across a range of helping behaviors, including financial, gifts, transportation, housework and yard work, and technology. The pattern does not hold for brothers. Possible explanations include resource dilution (daughters drawing more on parents' resources, leaving fewer resources to go around) or cooperative networks created among sisters (thus rendering aid from parents less necessary).